IMPLEMENTATION OF DIFFERENTIATED LEARNING THROUGH THE TEACHING AT THE RIGHT LEVEL (TARL) APPROACH IN FIFTH GRADE SCIENCE LESSONS AT SDN LENTENG AGUNG 07 PAGI - Anandea Nabilah Rizqy; Fauziyah Fadel Wardani; Nazilah Izhar Nursy; Putri Nadia; Sumiati (CV. Fahr Publishing, 2025)
This study aims to describe the implementation of differentiated learning through the Teaching at the Right Level (TaRL) approach in the 5th-grade science subject at SDN Lenteng Agung 07 Pagi. The study used a quantitative descriptive method with data collection techniques including observation, interviews, and documentation with the 5th-grade science teacher and all students. The data were analyzed using descriptive statistics to assess the implementation of differentiation across four main aspects: content, process, product, and learning environment. The results showed that all 14 indicators of differentiated learning were implemented 100%. Teachers adjust the material based on diagnostic assessments, carry out different learning activities according to students' abilities, provide a variety of learning product formats, and create a flexible and inclusive learning environment. The conclusion of the research states that the TaRL approach is implemented very well because all elements of differentiation are fully achieved, making science learning more adaptive, equitable, and capable of meeting the learning needs of each student.